Study designs and statistical approaches to suicide and prevention research in real-world data. - Lavigne, Jill E.; Lagerberg, Tyra; Ambrosi, John W.; Chang, Zheng (Suicide & Life-Threatening Behavior, 2021)
Objective: To provide researchers, clinicians and policy makers with a primer to study designs, statistical approaches and graphical reporting methods for suicide research in real world data (RWD).Methods: Study designs, statistical method and graphical reporting standards are detailed with examples from the recently published literature.Results: Data sources and codes for identifying suicidal behavior are described. Study designs are described in detail for post-market surveillance, retrospective cohort studies, case control and nested case-control studies, and self-controlled (within-individual) studies including applications of marginal structural models. Graphical reporting of designs is described using an original research study.Conclusions: Compared to RCTs, RWE studies offer larger sample sizes, greater generalizability, and real-world validity. However, these non-experimental data risk uncontrolled confounding and potential introduction of bias unless data, design and statistical approaches are rigorously aligned.